UNIT 15.7 cgpPindel: Identifying Somatically Acquired Insertion and Deletion Events from Paired End Sequencing. Issue 1 (17th December 2015) - Raine, Keiran M.; Hinton, Jonathan; Butler, Adam P.; Teague, Jon W.; Davies, Helen; Tarpey, Patrick; Nik‐Zainal, Serena; Campbell, Peter J.
Abstract : cgpPindel is a modified version of Pindel that is optimized for detecting somatic insertions and deletions (indels) in cancer genomes and other samples compared to a reference control. Post‐hoc filters remove false positive calls, resulting in a high‐quality dataset for downstream analysis. This unit provides concise instructions for both a simple 'one‐shot' execution of cgpPindel and a more detailed approach suitable for large‐scale compute farms. © 2015 by John Wiley & Sons, Inc.